Genetic variability of Begonia longifolia Blume from Indonesia based on Nuclear DNA internal transcribed spacer (ITS) sequence data - Wahyu Dewi Astuti Ningrum; Muhammad Bima Atmaja; Budi Setiadi Daryono; Purnomo PURNOMO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract.Ningrum WDA, Atmaja MB, Daryono BS, Purnomo. 2020. Genetic variability of Begonia longifolia Blume from Indonesia based on Nuclear DNA internal transcribed spacer (ITS) sequence data. Biodiversitas 21: 5778-5785. Begonia longifolia Blume is a member of the Begoniaceae family which has the widest distribution in Asia including Indonesia. Diversity studies on B.longifolia from Indonesia were mainly based on morphological characters. The genetic diversity analysis of this pantropical species in Indonesia has never been reported yet. This research aimed to study genetic variability of B. longifolia in Indonesia based on nuclear DNA internal transcribed spacer (ITS) sequence data. Twelve living specimens were from Sumatra (Lampung), Java (Sukabumi, Purwokerto), Bali (Buleleng, Gianyar, Jembrana, Tabanan), and Lombok. The 831-839 length sequence was aligned using Mesquite software. Reconstruction of the phylogenetic tree was done by MEGA7 software using Neighbor-Joining method with Kimura-2-Parameter. The 827 fixed sites showed a genetic distance ranged from 0 to 1.6%. Among the 827 sites compared, 802 sites were invariable, 19 sites were variable (11 singleton variable sites and 8 parsimony informative sites) and 6 sites were gaps. The phylogenetic tree showed 1 clade and 6 sub-clades. Specimens from Sumatra and Java formed a single sub-clade, separate with five sub-clades from Bali. Specimen from Lombok belong to one of the sub-clades of the Bali specimens. All specimens can be divided into 2 groups: Sumatra-Java and Bali-Lombok group.